Molecular Beam Epitaxy of Catalyst-Free InAs nanowires on Si (111) - Fadaly, Elham (My University, 2015)
Semiconductor nanowires (NWs) represent a unique system for exploring phenomena at the nanoscale and are also expected to play a critical role in future electronic and optoelectronic devices. For some functional NW-based devices, it is essential to have control over position, size and directionality of NWs for homogeneous and predictive performance. Moreover, the growth of device-quality NWs with high purity should abstain from conventional nucleation schemes that employ foreign catalyst such as gold. Recent progress in selective-area epitaxy (SAE) technique has allowed position controlled catalyst-free growth of NWs, where semiconductor substrates are masked by dielectrics with nano-aperture patterns. This is a kind of template method, which involves a combination of bottom up (epitaxial growth) and top down (lithography) approaches. However, the current approaches for the nano-patterning are mainly based on electron beam lithography (e-beam), which is expensive and not suitable for large scale productions. In this master’s thesis, we demonstrate the molecular beam epitaxy (MBE) of catalyst free InAs NWs on Si (111) by different techniques. The first technique adapts a fully bottom-up approach for selective-area molecular beam epitaxy (SA-MBE) growth of catalyst-free InAs NWs. Specific to this work, the inexpensive, versatile and simple colloidal lithography technique is applied for opening nano-apertures in a SiO2 layer deposited on Si substrates, and methods to have control over the size and density of patterns were studied. In the second approach, epitaxy of non-ordered catalyst-free InAs NWs was demonstrated on substrates without lithography patterning. This is realized by generating pinholes in the SiO2 layer using wet etching.
Keywords: Informations- och kommunikationsteknik; Materialvetenskap; Nanovetenskap och nanoteknik; Materialteknik; Nanoteknik; Information & Communication Technology; Materials Science; Nanoscience & Nanotechnology; Materials Engineering; Nano Technology